Islamic Microfinance Enterprise - saad al-harran (a.s noordeen, 2014)
This book attemps to explore solutions through the case studies that illustrate that islamic microfinance based on profit and loss sharing system that fund innovation and new business ventures can lead to wealth creation and coorperation among people of different cultural backgrounds.